Influence of the air gap between two cells of the storage battery on the thermal conditions of its operation: Numerical analysis and reliability assessment; Journal of Electroanalytical Chemistry; Vol. 945 - Kuznetsov G. V. Geny Vladimirovich (2023, 2023)
Title screen